Circulating Endothelial Cells are Associated with Thromboembolic Events in Patients with Antiphospholipid Antibodies - Foret, Thomas; Dufrost, Virginie; Heymonet, Marie; Risse, Jessie; Faure, Gilbert C.; Louis, Huguette; Lagrange, Jeremy; Lacolley, Patrick; Devreese, Katrien; Gibot, Sébastien; Regnault, Veronique; Zuily, Stéphane; Wahl, Denis (Thrombosis and Haemostasis, 2022)
Background Endothelial damage has been described in antiphospholipid antibody (aPL)-positive patients. However, it is uncertain whether circulating endothelial cells (CECs)—which are released when endothelial injury occurs—can be a marker of patients at high risk for thrombosis.Methods Ninety-seven patients with aPL and/or systemic lupus erythematosus (SLE) were included. CECs were determined by an automated CellSearch system. We also assayed plasma levels of tissue factor-bearing extracellular vesicles (TF+/EVs) and soluble triggering receptor expressed on myeloid cells 1 (sTREM-1) as markers of endothelial dysfunction/damage.Results Patients' mean age was 46.1 ± 13.9 years, 77 were women. Thirty-seven had SLE and 75 patients were suffering from antiphospholipid syndrome. Thirty-seven percent of patients presented a medical history of arterial thrombosis and 46% a history of venous thromboembolism (VTE). Thirteen patients had increased levels of CECs (>20/mL), with a mean CEC level of 48.3 ± 21.3 per mL. In univariate analysis, patients with obesity or medical history of myocardial infarction (MI), VTE, or nephropathy had a significant increased CEC level. In multivariate analysis, obesity (odds ratio [OR] = 6.07, 95% confidence interval [CI]: 1.42–25.94), VTE (OR = 7.59 [95% CI: 1.38–41.66]), and MI (OR = 5.5 [95% CI: 1.1–26.6)] were independently and significantly associated with elevated CECs. We also identified significant correlations between CECs and other markers of endothelial dysfunction: sTREM-1 and TF+/EVs.Conclusion This study demonstrated that endothelial injury assessed by the levels of CECs was associated with thromboembolic events in patients with aPL and/or autoimmune diseases.
Keywords: antiphospholipid syndrome; circulating endothelial cells; thrombosis; microvesicles; sTREM-1